Analysis of Catalytic Material Effect on the Photovoltaic Properties of Monolithic Dye-sensitized Solar Cells - Natalita Maulani Nursam; Ade Istiqomah; Jojo Hidayat; Putri Nur Anggraini; Shobih - (Jurnal Elektronika dan Telekomunikasi, 2017)
Dye-sensitized solar cells (DSSC) are widely developed due to their attractive appearance and simple fabrication processes. One of the challenges that arise in the DSSC fabrication involves high material cost associated with the cost of conductive substrate. DSSC with monolithic configuration was then developed on the basis of this motivation. In this contribution, titanium dioxide-based monolithic type DSSCs were fabricated on a single fluorine-doped transparent oxide coated glass using porous ZrO2 as spacer. Herein, the catalytic material for the counter-electrode was varied using carbon composite and platinum in order to analyze their effect on the solar cell efficiency. Four-point probe measurement revealed that the carbon composite exhibited slightly higher conductivity with a sheet resistance of 9.8 Ω/sq and 10.9 Ω/sq for carbon and platinum, respectively. Likewise, the photoconversion efficiency of the monolithic cells with carbon counter-electrode almost doubled the efficiency of the cells with platinum counter-electrode. Our results demonstrate that carbon could outperform the performance of platinum as catalytic material in monolithic DSSC.